2018
DOI: 10.1007/s10068-018-0471-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of jupcheong (soaking in syrup) with ginger powder on the lipid oxidation and antioxidant stability of yakgwa (Korean deep-fried confection)

Abstract: This study evaluated the effect of jupcheong (soaking in syrup) with/without ginger on lipids and antioxidants of yakgwa (Korean deep-fried confection) during storage. Yakgwa was prepared with a dough consisting of wheat and rice flour (1:1, w/w), sesame oil, and sugar syrup. Shaped dough pieces were consecutively deep-fried in soybean oil at 90 and 150 °C, soaked in syrup with/without ginger powder, and stored at 30 °C in the dark for 8 weeks. Lipid oxidation was evaluated by peroxide and p-anisidine values, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This result was similar to a previous research. Oh et al ., (2019) fried dough consisting of wheat flour and honey in soybean oil at 150°C for 5 min and found that its p‐AV was 5.24. During the 7 days of storage, the p‐AV of the control samples increased from 9.76 to 13.67 ( P < 0.05), while the p‐AV of the coated samples increased from 7.53 to 11.12 ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…This result was similar to a previous research. Oh et al ., (2019) fried dough consisting of wheat flour and honey in soybean oil at 150°C for 5 min and found that its p‐AV was 5.24. During the 7 days of storage, the p‐AV of the control samples increased from 9.76 to 13.67 ( P < 0.05), while the p‐AV of the coated samples increased from 7.53 to 11.12 ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%